Allometric functions for apple banana leaf area and above ground biomass - Nowembabazi, Anna; Taulya, Godfrey; Tinzaara, William (Academic Journals, 2021)
The article describes how allomentric functions can be used to estimate apple banana leaf area and above ground biomass.